Hidden species diversity of Australian burrowing snakes (Ramphotyphlops). (4th July 2013) - Marin, Julie; Donnellan, Stephen C.; Hedges, S. Blair; Puillandre, Nicolas; Aplin, Ken P.; Doughty, Paul; Hutchinson, Mark N.; Couloux, Arnaud; Vidal, Nicolas
Abstract : The worm‐like snakes (Scolecophidia; approximately 400 nominal extant species) have a conservative morphology and are among the most poorly‐known terrestrial vertebrates. Although molecular evidence has helped determine their higher‐level relationships, such data have rarely been used to discriminate among species. We generated a molecular data set for the continental Australian blindsnakes (genus Ramphotyphlops ) to determine the concordance of molecular and morphological information in the taxonomic recognition of species. Our dataset included 741 specimens morphologically attributed to 27 nominal Ramphotyphlops species. We proposed species hypotheses (SHs) after analysis of sequences from a variable mitochondrial gene ( cytochrome b ) and examined these SHs with additional evidence from a nuclear gene ( prolactin receptor ) and geographical data. Although the nuclear marker was not as fast‐evolving and discriminating as the mitochondrial marker, there was congruence among the mitochondrial, nuclear, and geographical data, suggesting that the actual number of species is at least two times the current number of recognized, nominal species. Several biogeographical barriers and complex phytogeographical and geological patterns appeared to be involved in the division of some burrowing snake populations and, by consequence, in their diversification and speciation through isolation. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 110, 427–441.